Meso- and microporous carbon electrode and its effect on the capacitive, energy and power properties of supercapacitor - Erman Taer; R. Taslim; Sugianto Sugianto; M. Paiszal; Mukhlis Mukhlis; W. S. Mustika; Agustino Agustino (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Activated carbon monoliths (ACMs) with average pore diameters in the meso- and micropore regions were successfully produced from biomass material. ACM synthesis uses chemical activation with KOH and ZnCl2 activating agents. The carbon and activating agent mass ratios were 1:1, 1:3, 1:5 and 1:7. Both activating materials produced an ACM with an average pore diameter of 3.2 nm. The specific capacitance, specific surface area, energy and power were as high as 63 F/g, 650 m2/g, and 0.23 Wh/kg for KOH and 73 F/g, and 522 m2/g, and 19 W/kg for ZnCl2 activating agents, respectively. For comparison, we also studied the physical and electrochemical properties of ACM with an average pore size in the micropore range from the same raw material.